Male and undernourished children were at high risk of anemia in Ethiopia: a systematic review and meta-analysis - Mulugeta Melku; Wubet Worku Takele; Degefaye Zelalem Anlay; Daniale Tekelia Ekubagewargies; Zegeye Getaneh; Molla Abebe; Zegeye Abebe (BMC, 2018)
Abstract Background Anemia is one of the global public health problems affecting more than one-third of the world population. It has been strongly associated with limited psychomotor development; and poor growth and performance in cognitive, social, and emotional function in children. Despite published data revealed that anemia is a public health problem among children in Ethiopia, there is no a pooled national estimate on the prevalence and associated risk factors of anemia. Methods Published articles until December 31, 2017, were searched using comprehensive search strings through PubMed/Medline, EMBASE, SCOPUS, HINARI, Web of Science, Google Scholar and Google. Reference probing of published articles and hand searching were employed for grey literature. Two groups of review authors independently appraised the studies for eligibility and extracted the data. The quality of articles was assessed using Joana Brigg's institute critical appraisal checklist for prevalence and analytical studies. The pooled estimates were determined using random effect model. Heterogeneity between the included studies was assessed using the I2 statistics. Subgroup analysis was employed in the evidence of heterogeneity. Publication bias was assessed by visual inspection of the funnel plot and Egger's regression test statistic. Results Of the total 871 articles retrieved, 34 articles which involved 61,748 children were eligible for meta-analysis. The overall pooled prevalence of anemia using random effect model was 31.14% (95% CI: 24.62, 37.66%). In subgroup analysis, the pooled prevalence of anemia was higher among preschool-aged children (44.17%; 95% CI: 37.19, 51.15%) than school-aged children (22.19%; 95% CI: 17.54, 26.83%). Furthermore, the odds of anemia was higher among children who were male (OR = 1.11; 95% CI: 1.03, 1.19), stunted (OR = 1.95; 95% CI: 1.52, 2.51), and wasted (OR = 2.05; 95% CI: 1.36, 3.10). Conclusion The pooled prevalence of anemia among children was high, indicating that it had been continuing to be a public health problem. Therefore, there is a need to design a comprehensive prevention and control strategies to reduce its burden.